Republic of Congo : Fifth and Sixth Reviews Under the Three-Year Arrangement Under the Extended Credit Facility and Financing Assurances Review: Staff Report; Staff Statement and Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Congo. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
In this study, macroeconomic development, its performance, and outlook are reviewed. Narrowing of the infrastructure gap and public financial management (PFM) are focused to safeguard investment quality. Fiscal reform has been introduced to improve the design of the tax system and to strengthen fiscal institutions that the FAD technical assistance (TA) mission introduced. A comprehensive action plan has been introduced to improve the business climate. The outstanding debt issues are being resolved.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet